WSN-aided haze pollution governance: modelling public willingness based on structural equations. (2019) - Chen, Jibo; Song, Yingxi; Wang, Guizhi; Liu, Qi
Wireless sensor networks (WSNs) have been well investigated and widely used in environmental surveillance, climate data collection, etc. However, research on statistical analysis and decision making aided by WSNs, especially in the area of environmental hazards and risk governance, are rarely presented. In this paper, common factors are extracted, among which the optimal model of haze governance willingness is designed using structural equation modelling (SEM). The relationships between the influencing factors of public haze governance willingness are then analysed. The results show that haze governance and willingness will be affected by the perception of haze risk, quality, measurements and economic expenditure factors. The life impact, travel inconvenience, maximum duration, and the suffering times from haze are the most basic factors affecting haze governance willingness. To achieve the governance of haze, haze measurement and monitoring via a WSN-based network with the collaboration from the public will be feasible and effective.